The North-South differential and the migration of heterogeneous labor - Bellante, Don (American Economic Review, 1979)
The differential in median income or earnings between the North and South of the United States has persistently intrigued economists. The consensus view is that: (a) the North-South differential is substantial and has stubbornly persisted through time; and (b) while the labor force responds somewhat to regional pay differentials the response is not adequate enough to eliminate the differential within a reasonable period of time since outmigration from low- wage areas is frequently nearly cancelled out by simultaneous inmigration. The consensus view that the labor market is an inefficient allocator of the human resource has been questioned by Philip Coelho and Moheb Ghali in the only study investigating real wage differences. When controlling for industry mix at the two-digit level they found no significant difference between the North and South in average real wages of production works in manufacturing. However economists are not prone to discard firmly held conclusions on the basis of a single item of research. For example a study by Paul Lande and Peter Gordon ignores regional price level variations in finding at best very weak support for the neoclassical hypothesis of converging wage levels. Thus the purpose of this paper is to provide additional evidence on the real North-South differential. Specifically this paper examines an alternative source of data the 1970 Census in order to determine whether more recent and comprehensive data subjected to a different methodology will tend to support or contradict the findings of Coelho and Ghali. In Section I it is argued that analysis of the North-South differential and its migration consequences requires a recognition of the heterogeneous nature of labor. Section II analyzes the statistical findings on the ratio of southern to northern earnings both in the aggregate and in terms of relatively homogeneous subgroups. The migration patterns of the subgroups are also investigated. Conclusions are drawn in Section III. The results are consistent with a neoclassical model of heterogeneous labor. (excerpt)